Breeding behavior of radiation-induced effects in organic materials and their possible use as radiation dosimeters. (March 2021) - Abdelaal, Saad; Abdelhady, A.M.; Tokhy, Hatem Hussny; Eid, A.M.; Rammah, Y.S.; Awad, El-Sayed Mahmoud; Elmaghraby, Elsayed K.
Abstract: The present study reveals a deep association between the effects of gamma rays in irradiated organic substances and the age of the material after exposure. The late effects of radiation-induced modifications in polymeric material were investigated by means of the infrared signature and correlation with ultraviolet absorption. Detectors made of poly(allyl diglycol carbonate) were irradiated with doses between 500 Gy and 5 MGy and compared by means of similar samples aged 8 and 12 years. Infrared investigation showed the differences between infrared spectra recorded directly after irradiation and those recorded for the aged samples. The aging effect was found to be minor at low doses. For samples irradiated at high doses, the material digested itself through processes that have radiation breeding-fermentation behavior. Ultraviolet absorption revealed the presence of a hyperchromic effect and a bathochromic shift in connection with the age of these samples. This breeding behavior of radiation-induced effects in organic materials should be taken into account in dosimetry. Highlights: Quantitative measurements of the late effect of radiation-induced modifications in polymeric material. Investigated samples are newly exposed samples and samples aged 8–12 years originally irradiated with doses up to 5 MGy. The hyperchromic effect and the bathochromic shift were investigated in relation to time since exposure. Breeding behavior of radiation-induced effects in organic materials was recommended to be taken into account in the design for industrial purposes.